ANALISIS STRUKTUR KRISTAL LIMBAH MAGNET PERMANEN BERBASIS BESI OKSIDA - Cynthia Sagita; Mutia Delina; Erfan Handoko (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
Has performed the initial characterization of BaFe12O19 wasted magnet (Barium Hexaferrite). Characterization has done by analyzing the crystal structure using X-Ray Difraction (XRD). The analysis showed that the sample is a single phase, namely BaFe12O19. Samples with a hexagonal crystal structure (space group P63 / mmc), lattice parameters a = b = 5.892 Å, c = 23.183 Å with and . Samples also have the atomic density of 5.32 and the unit cell volume 693.608 with a crystal size of 632.7 Å. The results showed BaFe12O19 wasted can be reused as a new magnet material. Key word: Barium Hexaferrite, magnet wasted, crystal structure and XRD.